Endophytic Fusarium oxysporum GW controlling weed and an effective biostimulant for wheat growth - Asim, Syed; Hussain, Anwar; Murad, Waheed; Hamayun, Muhammad; Iqbal, Amjad; Rehman, Hazir; Tawab, Abdul; Irshad, Muhammad; Alataway, Abed; Dewidar, Ahmed Z.; Elansary, Hosam O.; Lee, In-Jung (Frontiers in Plant Science, 2022)
Weed control is an integral part of agricultural practices and growing wheat is no exception. This crop is challenged by several weeds which claim for significant yield losses. Avena Fatua is a noxious weed, common in wheat field where this weed alone is responsible for 30% losses in yield annually. Because of the environmental concerns, researchers are in a continuous hunt to find clean alternatives in order to manage weeds. Fungi have shown promising weedicide potential in lab studies. The current study aimed to isolate endophytic fungi from wheat plants which can promote wheat growth and inhibit growth of a common weed, Avena fatua. Of several isolates, GW was selected for its promising features and the strain was identified as F. oxisporum through ITS sequencing technique. This fungus released a number of compounds including Isovitexin, Calycosin, quercetagetin and dihydroxy-dimethoxyisoflavone that inhibited growth of A. fatua but did not influence growth of wheat seedlings. Biomass of this fungus in the soil also reduced growth parameters of the weed and promoted growth of wheat. Behind this differential response of the two plants were their contrasting physiological and biochemical status. This contrast was evident from phytohormones profile and antioxidant potential which might be the reason behind their contrasting phenotypes.